2015
DOI: 10.3233/ch-131742
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the hematocrit-to-viscosity ratio and microvascular oxygenation in brain and muscle?

Abstract: The hematocrit-to-viscosity ratio (HVR) has been widely used has an estimate of red blood cell (RBC) oxygen transport effectiveness into the microvasculature or as an oxygen delivery index. However, no study investigated the possibility of HVR to truly reflect RBC oxygen transport effectiveness or to be an oxygen delivery index. We measured blood viscosity at high shear rate (225 s −1 ), hematocrit, HVR, as well as the microvascular oxyhemoglobin saturation (TOI; tissue oxygen index) by spatial resolved near-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…This might be explained by the absence of differences in Hb levels before and after HD; however, it was recently reported that cerebral oxygenation did not improve even with the significant increase in Hb levels induced by ultrafiltration during HD [7, 8]. Regarding the differences in changes in cerebral oxygenation between Hb increases by intradialytic blood transfusion and those by ultrafiltration during HD, the reasons might be explained by the changes in hematocrit-to-viscosity ratios [20] during HD. However, in this study, plasma viscosity was not measured; therefore, we cannot conclude an association between its ratio and changes in cerebral oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the absence of differences in Hb levels before and after HD; however, it was recently reported that cerebral oxygenation did not improve even with the significant increase in Hb levels induced by ultrafiltration during HD [7, 8]. Regarding the differences in changes in cerebral oxygenation between Hb increases by intradialytic blood transfusion and those by ultrafiltration during HD, the reasons might be explained by the changes in hematocrit-to-viscosity ratios [20] during HD. However, in this study, plasma viscosity was not measured; therefore, we cannot conclude an association between its ratio and changes in cerebral oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Oxygen transport effectiveness has been analyzed in recent years theoretically, 37 experimentally ex vivo [38][39][40] and in vivo. 41 We have previously calculated theoretical oxygen transport effectiveness to assess optimal Hct values viscometrically and with the AMVN device. 42 In the present study, estimated oxygen transport effectiveness was highest at a Hct feeding of approximately 60% in all capillary microchannels studied ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although vascular function seems to be better preserved in children with SC, both sickle cell groups had a decreased exercise capacity compared to healthy children. In SC, mild anaemia and blood hyperviscosity could be responsible for decreased physical fitness, due to their known adverse effects on tissue oxygenation [64].…”
Section: Physical Activity Level and Fitnessmentioning
confidence: 99%